Keynes : the rise, fall, and return of the 20th century's most influential economist - Clarke, P. F. (Bloomsbury Press, 2009)
The ideas of John Maynard Keynes inspired the New Deal and helped rebuild world economies after World War II--and were later dismissed as "depression economics." Then came the great meltdown of 2008. Market forces that the world relied on suddenly failed to self-correct--and Keynes's doctrine of corrective action in an imperfect world became more relevant than ever. Keynes was not a traditional economist: he was a polemicist, an iconoclastic public intellectual, a peer of the realm, and a political operative, as well as an openly homosexual bohemian who befriended Virginia Woolf and E. M. Forster. Here, historian Peter Clarke provides a timely accounting of Keynes's life and work, bringing his genius and skepticism alive for an era fraught with economic difficulties that he surely would have relished solving.--From publisher description.